Projecto de reabilitação de imóvel histórico no tecido urbano de Lisboa : caso de estudo de edifício Pombalino na Rua da Madalena, Baixa Chiado - Mexia, Duarte Morgado Ferreira Marques 1989- (2015)
his dissertation aims to examine the constant need of rehabilitation in the arquiteture of Lisbon, especially in historic areas, and the consequent role of the Interior Designer can/must explore in this process. To analyze the framework of the city, the history, social and cultural (heritage), will be made jointly with processes and rehabilitation programs currently used. We analyze the characteristics used to define the rehabilitation and contextualized its meanings. We define the challenges that rehabilitation exposes in its implementation, and respective current needs. It will reflect on the changes in ways of living and housing, and residential buildings as "Pombalino" style has the ability to adapt to the needs and demands of users today. In Lisbon, and specially the "Madalena" Street will be the focus for a more targeted and specific study, not to stop this study for a just generalist approach. The Analyze of this kind of housing built in this area, the issues that mark the contemporary, as well as the potential that can regeneration from the same are the target of this study. Together with the analyze of the errors described by others autors it's made a study of implementation and maintenance for the rehabilitation. It seeks to demonstrate that, for the realization of a regenerative process, as in the case of a rehabilitation project, it is necessary for this, an interior Designer that takes into account all the knowledge and methodologies used in this type of intervention. To accomplish this, the professional must master questions and problems solving and construction techniques for the application of new materials, as well as the new attitude of organizing space and new features will be emphasized